The hidden potential of boredom – How does the relative perception of boredom influence concentration and task performance? - Joshua W. Coen (Junior Management Science (JUMS), 2023)
As boredom in the workplace is an important factor with widespread consequences, research interest in this topic is very high. This paper proposes a way of decreasing workplace boredom and thereby the negative effects associated with it. Based on literature about contrast effects, this paper develops the hypothesis that contrast between boredom levels leads to higher or lower evaluations of task boredom in a subsequent cognitive task. In an online experiment, this theory was tested. The results show that the same task is perceived as less boring when preceded by a monotonous and unchallenging task. An opposite effect for highly interesting tasks could not be determined. In addition, it was found that the boredom induction is linked to significantly lower concentration and that both boredom and inattention decrease cognitive performance. As proposed, the performance influence of boredom transcended tasks, with task C boredom fully mediating the relationship between task 1 boredom and cognitive performance. Further insights and implications are discussed, including a possible bidirectional causal relationship between boredom and inattention. The results implicate that boredom can be deliberately influenced through contextual cues and task order to mitigate its disadvantages.
Keywords: 650; Boredom; Productivity; Work design; Concentration; Contrast effects